Epidemiology, clinical spectrum, viral kinetics and impact of COVID‐19 in the Asia‐Pacific region. Issue 4 (9th March 2021) - Kwok, Kin On; Huang, Ying; Tsoi, Margaret Ting Fong; Tang, Arthur; Wong, Samuel Yeung Shan; Wei, Wan In; Hui, David Shu Cheong
ABSTRACT: COVID‐19 has hit the world by surprise, causing substantial mortality and morbidity since 2020. This narrative review aims to provide an overview of the epidemiology, induced impact, viral kinetics and clinical spectrum of COVID‐19 in the Asia‐Pacific Region, focusing on regions previously exposed to outbreaks of coronavirus. COVID‐19 progressed differently by regions, with some (such as China and Taiwan) featured by one to two epidemic waves and some (such as Hong Kong and South Korea) featured by multiple waves. There has been no consensus on the estimates of important epidemiological time intervals or proportions, such that using them for making inferences should be done with caution. Viral loads of patients with COVID‐19 peak in the first week of illness around days 2 to 4 and hence there is very high transmission potential causing community outbreaks. Various strategies such as government‐guided and suppress‐and‐lift strategies, trigger‐based/suppression approaches and alert systems have been employed to guide the adoption and easing of control measures. Asymptomatic and pre‐symptomatic transmission is a hallmark of COVID‐19. Identification and isolation of symptomatic patients alone is not effective in controlling the ongoing outbreaks. However, early, prompt and coordinated enactment predisposed regions to successful disease containment. Mass COVID‐19 vaccinations are likely to be the light at the end of the tunnel. There is a need to review what we have learnt in this pandemic and examine how to transfer and improve existing knowledge for ongoing and future epidemics.